The Role and Function of the Madrasah Principal as an Educational Leader at the PUI Haurkolot Private Elementary Madrasah - Fatihul Fauzi; Kambali; Suklani (al-Afkar, Journal For Islamic Studies, 2026)
The purpose of this study is to examine the role and function of the madrasah principal as an educational leader at MIS PUI Haurkolot. This research uses a qualitative descriptive approach and employs a literature review as its research model. Data collection methods include document analysis and key informant interviews. The study found that the principal plays a significant role in managing the school, cultivating a conducive learning environment, and promoting Islamic values. Data analysis indicates that effective leadership, characterized by a clear vision, strong communication, and collaborative behavior, enhances overall school performance. This study concludes that the principal's leadership has an impact on academic performance, student discipline, and the school's reputation. This research recommends that future research focus on the influence of leadership styles on student learning outcomes and the development of leadership training programs for educational leaders.